2019
DOI: 10.1017/s037346331800108x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Environmental Engagement with Natural Language Interfaces for In-Vehicle Navigation Systems

Abstract: Four on-road studies were conducted in the Clifton area of Nottingham, UK, aiming to explore the relationships between driver workload and environmental engagement associated with ‘active’ and ‘passive’ navigation systems. In a between-subjects design, a total of 61 experienced drivers completed two experimental drives comprising the same three routes (with overlapping sections), staged one week apart. Drivers were provided with the navigational support of a commercially-available navigation device (‘satnav’),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…[178] Therefore, studies have been done wherein the driver and the VA are engaged in a casual conversation rather than information gathering sequence of voice commands and have shown that it can be effective in preventing driver distraction. [179][180][181] Studies showed that short intermittent conversation with a VA can help increase driver alertness. [179] Furthermore, driving simulator-based studies has been performed to show that VAs should provide assertive voices to grab driver attention.…”
Section: Voice-based Interactionmentioning
confidence: 99%
“…[178] Therefore, studies have been done wherein the driver and the VA are engaged in a casual conversation rather than information gathering sequence of voice commands and have shown that it can be effective in preventing driver distraction. [179][180][181] Studies showed that short intermittent conversation with a VA can help increase driver alertness. [179] Furthermore, driving simulator-based studies has been performed to show that VAs should provide assertive voices to grab driver attention.…”
Section: Voice-based Interactionmentioning
confidence: 99%
“…Linguistics refers to papers that explore text similarities, such as identifying place entities (Gupta, Ayyar, Singh, & Shah, 2018; Thenmozhi, Senthil Kumar, & Aravindan, 2018; Zhu, 2017) and spatial relationships (Prendergast & Szafir, 2018) in unstructured texts. Improving navigation is vital for location‐aware virtual assistants, be that in indoor contexts (Dobnik & Pulman, 2010; Subramani & Deepika, 2019) or outdoor spaces (Antrobus, Large, Burnett, & Hare, 2019; Cuayáhuitl & Dethlefs, 2011). Finally, improving the conversation and understanding the subtle emotions in the communication between humans and assistants (Portela & Granell‐Canut, 2017) is a primary research line regardless of the target application domain.…”
Section: Resultsmentioning
confidence: 99%
“…Among these 12 named virtual assistants, only four (SpaceBook—Bartie et al, 2018; Paval—Massai et al, 2019; TITERIA—Garrido et al, 2017; Trip 4 All—Signoretti et al, 2015) have to do with tourism‐related activities, followed by recommendation or decision‐making support (Loki—Ronzhin et al, 2019; CitiCafe—Atreja et al, 2018), healthcare (MIRob—Bandara et al, 2018; PeopleBot—González‐Medina et al, 2019), and education (CAGA—Cai et al, 2013; TreasureHuntBot—Klopfenstein et al, 2018a). Finally, Diana (Tsai, Chen, & Kang, 2019), which is related to disaster management, and Satnav (Antrobus et al, 2019), which explores relationships between driver workload and environmental engagement‐associated navigation systems, are categorized differently, even though they could still be seen under the recommendation‐related application domain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This work has revealed that an on-board agent with whom the driver can interact freely using conversational language can minimise cognitive demand and workload [7]. In addition, it can be an effective counter-measure to passive task-related fatigue [8,9], increase levels of trust and acceptance in autonomous vehicles [10,11] and enrich environmental engagement [12]. A particular challenge in conducting this work has been to create and deliver an 'authentic' CUI experience, not least to ensure that we do not violate users' high expectations of future technology or indeed how they expect, or would choose to interact.…”
Section: Introductionmentioning
confidence: 99%